2017
DOI: 10.1039/c7cc00961e
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable nanoporous films by loading azobenzene in metal–organic frameworks of type HKUST-1

Abstract: Photoswitchable metal-organic frameworks (MOFs) enable the dynamic remote control of their key properties. Here, a readily producible approach is presented where photochromic molecules, i.e. azobenzene (AB) and o-tetrafluoroazobenzene (tfAB), are loaded in MOF films of type HKUST-1. These nanoporous films, which can be reversibly switched with UV/visible or only visible light, have remote-controllable guest uptake properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 27 publications
2
90
0
Order By: Relevance
“…Compared with attempts to incorporate the photoactive functionality as a part of the backbone or a substituent of the linker used to construct the respective MOF, the approach to embed the photochromic molecule as a guest in the MOF framework has the advantage of an easy synthetic accessibility, as well as a very high versatility with respect to the MOF and the guest. One might object that the guest molecules are only weakly bonded to the MOF framework so that the thermal stability of the resulting guest@MOF systems is not high, but for azobenzene embedded in thin films of type HKUST‐1 it was shown that when stored at room temperature the guest leaves the MOF very slowly with a depletion (or desorption) time constant τ ≈360 days . However, when stored at 60 °C τ decreases significantly to 14.5 days .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with attempts to incorporate the photoactive functionality as a part of the backbone or a substituent of the linker used to construct the respective MOF, the approach to embed the photochromic molecule as a guest in the MOF framework has the advantage of an easy synthetic accessibility, as well as a very high versatility with respect to the MOF and the guest. One might object that the guest molecules are only weakly bonded to the MOF framework so that the thermal stability of the resulting guest@MOF systems is not high, but for azobenzene embedded in thin films of type HKUST‐1 it was shown that when stored at room temperature the guest leaves the MOF very slowly with a depletion (or desorption) time constant τ ≈360 days . However, when stored at 60 °C τ decreases significantly to 14.5 days .…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of E ‐ and Z ‐ tF ‐AZB were reported quite recently and compared with those of the other azobenzenes depicted in Scheme and 2 . For thin (SURMOF) films of type HKUST‐1 the successful incorporation of tF ‐AZB was already proven …”
Section: Introductionmentioning
confidence: 97%
“…The synthesis and design of functional hybrid switch@MOF materials has become a central point of research in recent years . These smart composites are obtained by introducing photoswitchable dye molecules such as azobenzenes and (fluorinated) derivatives, diarylethenes or spiropyrans as non‐covalently attached guests into the crystalline porous MOF (metal‐organic framework) host scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Introduction of azobenzene moieties in porous MOF-like materials has already been challenged in recent studies. [17,18] Thef irst alternative would be truly exciting but difficult to realize;t he challenges arise from the fact that azobenzene is an integral part of ar igid crystal structure in which the trans-cis transformation either does not occur owing to the lack of free space,o ro ccurs but destroys the crystal lattice in an irreversible manner. [17,18] Thef irst alternative would be truly exciting but difficult to realize;t he challenges arise from the fact that azobenzene is an integral part of ar igid crystal structure in which the trans-cis transformation either does not occur owing to the lack of free space,o ro ccurs but destroys the crystal lattice in an irreversible manner.…”
mentioning
confidence: 99%